Digital Comics: Character Value-Based Learning Media in the Ramayana Puppet Story Content Social Studies Elementary School - Candrayani, Ni Made Windya; Sujana, I Wayan (Indonesian Values and Character Education Journal, 2023)
The lack of variations in the teacher's digital learning media that are under the characteristics of teaching materials and student characteristics in social studies learning has resulted in student limitations as the impact of low self-learning. This study aims to analyze digital comics' design, validity, and effectiveness. This research is a development research adapting the ADDIE development model. The subjects of this study included four experts and students. Data collection was carried out using questionnaires and learning achievement tests. Both quantitative descriptive analysis and inferential statistical analysis were used for the data analysis. The design of digital comics involved five stages, namely analysis, design, development, implementation, and evaluation. Product validity was determined according to learning content experts who obtained very good qualifications, instructional design experts who obtained good qualifications, learning media experts who obtained very good qualifications, the results of individual trials who obtained very good qualification, and the results of small group trials obtained very good qualifications. According to the findings of the study, digital comics are appropriate for use in elementary schools.